Optical and colorimetrical characteristics of strained LiF crystals under X-ray irradiation - Petchenko, O.M.; Petchenko, G.О.; Boiko, S.М.; Bezugly, A.V. (Вопросы атомной науки и техники, 2020)
Here there were investigated the х-irradiation influence on the optical characteristics of LiF crystals and the colorimetric characteristics of optical radiation passing through crystals with different doses of irradiation. It was established that change of irradiation dose in the interval 0…1057 Р leads to reduce of absolute value of coordinates of the color and brightness of the radiation, passing through the crystal, but the color of the radiation thus remains constant. Досліджено вплив рентгенівського опромінення на оптичні характеристики кристалів LiF і колориметричні характеристики оптичного випромінювання, що проходить через кристали з різними дозами опромінення. Встановлено, що зміна дози опромінення в інтервалі 0…1057 Р призводить до зменшення за абсолютною величиною координат кольору і яскравості випромінювання, що проходить через кристал, але кольоровість випромінювання при цьому не змінюється. Исследовано влияние пластической деформации на оптические характеристики кристаллов LiF и колориметрические характеристики оптического излучения, проходящего через кристаллы с разными дозами облучения. Установлено, что изменение дозы облучения в интервале 0…1057 Р приводит к уменьшению по абсолютной величине координат цвета и яркости излучения, проходящего через кристалл, но цветность излучения при этом не изменяется.